Gen(d)eration Next: Prose by Julia Franck and Judith Hermann - Anke Biendarra (Studies in 20th & 21st Century Literature, 2004)
In March 1999, critic Volker Hage adopted a term in Der Spiegel that subsequently dominated public discussions about new German literature by female authors-"Fräuleinwunder"…
Keywords: 1999; Volker Hage; Der Spiegel; new German literature; female authors; Fräuleinwunder; Julia Franck; Judith Hermann; critic; gender; generation